Adequacy check of refractory design by FE modelling - Saha, P.; Pal, Prabhat; Sarkar, B.; Lahiri, P. (2014)
© 2014 The American Ceramic Society.Refractory lining in a furnace undergoes thermal and mechanical stresses during operation. The amount of thermal expansion and stresses need to be ascertained for a successful design and material selection. Finite element analysis is an important tool which can be utilized to assess the effect of expansion and stresses in a lining system and necessary guideline can be framed during design stage. This paper presents a case study of finite element analysis undertaken by the authors for an absorption tower refractory dome of a sulphuric acid plant. Refractory dome of sulphuric acid tower is a self supporting low rise dome made of double tapered bricks arranged in concentric rings. For the purpose of analysis, the dome is assumed to be uniform and cyclic-symmetric about the centre and FE modeling is done accordingly. The stress distribution in the refractory lining dome has been ascertained considering the mechanical and thermal load. The deformation and displacement behavior of dome refractory assembly under stress is studied and adequacy of the design verified.